Case Report: Chemotherapy-induced phlebitis in a dog: diagnostic approach and management strategies - Hwang, Seoyoung; Hong, Heejeong; Jung, Joohyun (Frontiers in Veterinary Science, 2025)
A 7-year-old neutered male Golden Retriever diagnosed with osteosarcoma of the left radius underwent limb amputation followed by adjuvant chemotherapy utilizing alternating carboplatin-doxorubicin protocols. Following doxorubicin administration, the patient exhibited localized heat, swelling, pain, and lameness in the right forelimb, indicative of phlebitis. Ultrasonography confirmed chemotherapy-induced phlebitis with thickening of the right cephalic vein wall, intraluminal thrombi, and significant perivascular edema. Treatment involved anti-inflammatory corticosteroids, oral medications (clopidogrel, pentoxifylline, doxycycline, vitamin E), and low-level laser therapy (LLLT), achieving clinical improvement. Despite successful control of chronic inflammation in the cephalic vein, phlebitis subsequently developed in other veins, including the right common dorsal digital vein and left saphenous vein, despite varying vascular access points. The patient showed clinical improvement with the combined use of oral medication and low-level laser therapy. The chemotherapy regimen was completed successfully without osteosarcoma recurrence, and the patient remained stable for over 13 months post-treatment. Following discontinuation of chemotherapy and supportive care, no further progression of phlebitis occurred. To the authors' knowledge, this report represents the first documented veterinary case of chemotherapy-induced phlebitis in a dog. While extensively reported in human oncology, chemotherapy-induced phlebitis remains underreported in veterinary medicine. Clinicians should recognize phlebitis as a potential complication associated with chemotherapeutic agents such as doxorubicin and carboplatin. Ultrasonography serves as an essential diagnostic and monitoring tool. Prophylactic corticosteroids and adjunctive low-level laser therapy offer promising preventative and therapeutic strategies, particularly for patients with predisposed vascular inflammation. This case underscores the importance of early identification, proactive management, and individualized treatment approaches to chemotherapy-associated phlebitis in veterinary oncology.